2016
DOI: 10.1002/ece3.2103
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of mating with siblings and nonsiblings on the reproductive success in a leaf beetle

Abstract: Choosing a suitable mating partner is crucial for the fitness of an individual, whereby mating with siblings often results in inbreeding depression. We studied consequences of mating with siblings versus nonsiblings in the mustard leaf beetle, Phaedon cochleariae (Coleoptera: Chrysomelidae), on lifetime reproductive traits. Furthermore, we analyzed whether cuticular hydrocarbon (CHC) profiles are family specific and could potentially influence the mating behavior of young adults. We hypothesized a reduced repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
(124 reference statements)
3
21
1
Order By: Relevance
“…The present study revealed that mustard leaf beetles suffer from strong inbreeding depression throughout their ontogeny. Inbreeding does not only reduce the larval hatching rate of the beetle as detected in a previous study (Müller & Müller, ), but also crucially increases the mortality of larvae prior adult emergence and of young adults. Moreover, the reproductive output of inbred females was reduced compared to outbred females, although their body mass was not decreased by inbreeding.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The present study revealed that mustard leaf beetles suffer from strong inbreeding depression throughout their ontogeny. Inbreeding does not only reduce the larval hatching rate of the beetle as detected in a previous study (Müller & Müller, ), but also crucially increases the mortality of larvae prior adult emergence and of young adults. Moreover, the reproductive output of inbred females was reduced compared to outbred females, although their body mass was not decreased by inbreeding.…”
Section: Discussionsupporting
confidence: 63%
“…In a previous study on P. cochleariae , we disclosed that the larval hatching rate of inbred offspring is decreased in comparison with outbred offspring (Müller & Müller, ). Thus, this beetle species suffers from inbreeding depression and we consequently expected negative inbreeding effects on other fitness‐related traits throughout its ontogeny.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Likewise, better survival has been reported in heterozygous individuals in birds (Velando, Barros, & Moran, ) and annelids (McElroy, Presley, & Diehl, ). Inbred crosses often result in a decrease in fertility (i.e., offspring number), as observed in arthropods (Lihoreau, Zimmer, & Rivault, ; Müller & Müller, ), and as a result offspring production is one of the life history traits that has received the most attention in the literature. It is likely that the homozygous state of loci with deleterious recessive alleles leads to a decrease in inbred offspring fitness (Charlesworth & Willis, ).…”
Section: Introductionmentioning
confidence: 99%